2016
DOI: 10.1016/j.cct.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to evaluate multi-dimensional effects of dance for people with Parkinson's disease

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disease associated with deficits in motor, cognitive, and emotion/quality of life (QOL) domains, yet most pharmacologic and behavioral interventions focus only on motor function. Our goal was to perform a pilot study of Dance for Parkinson’s—a community-based program that is growing in popularity—in order to compare effect sizes across multiple outcomes and to inform selection of primary and secondary outcomes for a larger trial. Study participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 57 publications
3
62
1
5
Order By: Relevance
“…Recent research on arts and health centres on how performing arts can best serve people living with debilitating and chronic illness such as dementia, Parkinson's disease, and mental illness (Adam, Ramli, & Shahar, 2016;Coaten & Newman-Bluestein, 2013;Guzman, Freeston, Rochester, Hughes, & James, 2016;Jones, 2016;Karkou & Meekums, 2017;Lannen, Worrall, Alston, Marley, & Allan, 2012;Lapum & Bar, 2016;Särkämö et al, 2016;Sorrell, 2018;Sung & Chang, 2005;Sung, Chang, & Lee, 2010;Verghese et al, 2006). For example, multiple studies have shown that dance therapy can significantly improve gait, movement, balance, and wellbeing in patients with Parkinson's disease (Butt, 2017;Hackney & Earhart, 2010;Hackney & McKee, 2014;Hashimoto, Takabatake, Miyaguchi, Nakanishi, & Naitou, 2015;Karkou & Meekums, 2017;Lewis, Annett, Davenport, Hall, & Lovatt, 2016;McNeely, Duncan, & Earhart, 2015;Rios Romenets, Anang, Fereshtehnejad, Pelletier, & Postuma, 2015;Rocha, Slade, McClelland, & Morris, 2017;Shanahan et al, 2017;Ventura et al, 2016). Music therapy is also a well-established approach to treating a range of issues, such as speech pathologies, poor mental health, and social and behavioural difficulties in children and adults (Edwards, 2011;MacDonald et al, 2012).…”
mentioning
confidence: 99%
“…Recent research on arts and health centres on how performing arts can best serve people living with debilitating and chronic illness such as dementia, Parkinson's disease, and mental illness (Adam, Ramli, & Shahar, 2016;Coaten & Newman-Bluestein, 2013;Guzman, Freeston, Rochester, Hughes, & James, 2016;Jones, 2016;Karkou & Meekums, 2017;Lannen, Worrall, Alston, Marley, & Allan, 2012;Lapum & Bar, 2016;Särkämö et al, 2016;Sorrell, 2018;Sung & Chang, 2005;Sung, Chang, & Lee, 2010;Verghese et al, 2006). For example, multiple studies have shown that dance therapy can significantly improve gait, movement, balance, and wellbeing in patients with Parkinson's disease (Butt, 2017;Hackney & Earhart, 2010;Hackney & McKee, 2014;Hashimoto, Takabatake, Miyaguchi, Nakanishi, & Naitou, 2015;Karkou & Meekums, 2017;Lewis, Annett, Davenport, Hall, & Lovatt, 2016;McNeely, Duncan, & Earhart, 2015;Rios Romenets, Anang, Fereshtehnejad, Pelletier, & Postuma, 2015;Rocha, Slade, McClelland, & Morris, 2017;Shanahan et al, 2017;Ventura et al, 2016). Music therapy is also a well-established approach to treating a range of issues, such as speech pathologies, poor mental health, and social and behavioural difficulties in children and adults (Edwards, 2011;MacDonald et al, 2012).…”
mentioning
confidence: 99%
“…A velhice traz à mulher maior possibilidade de ficar sozinha, sendo o elemento de referência familiar. 43 As mulheres têm maior probabilidade de enviuvar numa idade menos avançada, com muitos anos de vida ainda pela frente.…”
Section: Ganismounclassified
“…Four studies were non-randomized and therefore have an increased risk of bias. [32][33][34][35] The majority of RCTs and non-randomized studies have an increased risk of selection bias. 34,35,[37][38][39][40][41]43 Comparability between the groups at baseline was also lacking in four studies.…”
Section: Limitationsmentioning
confidence: 99%
“…34,36 The dance interventions were well-described in 10 studies. 35,40,41 Seven studies stated that a warm-up was performed at the start of class [31][32][33][34]36,39,42 and nine studies used dance instructors with previous experience. 31,33,[36][37][38][39][40]42,43 Two studies included a home dance program as part of the dance intervention.…”
mentioning
confidence: 99%
See 1 more Smart Citation